(untitled) (Medico Legal Update, 2020)
The terrorist financing activities are considered one of the most important threats that facing the security and safety of people of society in all its forms, as their danger increases by adopting a pattern of transnational organized crime. There is no longer planning, managing and implementing them is done within the territory of one country, but its lines are woven across multiple countries to conduct them in the targeted country with the crime. Iraq comes in the forefront of countries that suffered from terrorism and the violent crimes,in order to strike stability in it, also to sow discord and sectarian fighting for this, the Iraqi state must confront the terrorism in general, as well as the terrorist financing activities in particular, reducing its seriousness and punish the perpetrators, so, the Anti-Terrorism Law No. 13 of 2005, and the Anti-Money Laundering and Terrorist Financing Law No. 39 of 2015, was issued, as it was issued in implementation of Article 22 of the Money Laundering Law that was mentioned previously,this leads to the question about the adequacy of these legal texts to address the crime of financing terrorism, whether the Iraqi legislator succeeded in putting in place the necessary mechanisms with the appropriate part to prevent these funds for reaching to the hands of terrorist organizations.